Hypothalamic volume loss is associated with reduced melatonin output in Parkinson's disease. Issue 7 (12th March 2016) - Breen, David P.; Nombela, Cristina; Vuono, Romina; Jones, P. Simon; Fisher, Kate; Burn, David J.; Brooks, David J.; Reddy, Akhilesh B.; Rowe, James B.; Barker, Roger A.
ABSTRACT: Background: Recent studies have suggested that melatonin—a hormone produced by the pineal gland under circadian control—contributes to PD‐related sleep dysfunction. We hypothesized that degenerative changes to the neural structures controlling pineal function (especially the suprachiasmatic nuclei of the anterior hypothalamus) may be responsible for reduced melatonin output in these patients. We compared hypothalamic volumes in PD patients with matched controls and determined whether volume loss correlated with reduced melatonin output in the PD group. Methods: A total of 12 PD patients and 12 matched controls underwent magnetic resonance imaging to determine hypothalamic volume. In addition, PD patients underwent 24‐hour blood sampling in a controlled environment to determine serum melatonin concentrations using enzyme‐linked immunosorbent assays. Results: PD patients had significantly reduced hypothalamic gray matter volume when compared with matched controls. Melatonin levels were significantly associated with hypothalamic gray matter volume and disease severity in PD patients. Conclusion: Melatonin levels are associated with hypothalamic gray matter volume loss and disease severity in PD patients. This provides anatomical and physiological support for an intrinsic sleep and circadian phenotype in PD. © 2016 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society